Designing a fully automated multi‐bioreactor plant for fast DoE optimization of pharmaceutical protein production. Issue 6 (6th June 2013) - Fricke, Jens; Pohlmann, Kristof; Jonescheit, Nils A.; Ellert, Andree; Joksch, Burkhard; Luttmann, Reiner
Abstract The identification of optimal expression conditions for state‐of‐the‐art production of pharmaceutical proteins is a very time‐consuming and expensive process. In this report a method for rapid and reproducible optimization of protein expression in an in‐house designed small‐scale BIOSTAT® multi‐bioreactor plant is described. A newly developed BioPAT® MFCS/win Design of Experiments (DoE) module (Sartorius Stedim Systems, Germany) connects the process control system MFCS/win and the DoE software MODDE® (Umetrics AB, Sweden) and enables therefore the implementation of fully automated optimization procedures. As a proof of concept, a commercial Pichia pastoris strain KM71H has been transformed for the expression of potential malaria vaccines. This approach has allowed a doubling of intact protein secretion productivity due to the DoE optimization procedure compared to initial cultivation results. In a next step, robustness regarding the sensitivity to process parameter variability has been proven around the determined optimum. Thereby, a pharmaceutical production process that is significantly improved within seven 24‐hour cultivation cycles was established. Specifically, regarding the regulatory demands pointed out in the process analytical technology (PAT) initiative of the United States Food and Drug Administration (FDA), the combination of a highly instrumented, fully automated multi‐bioreactor platform with proper cultivation strategies and extended DoE software solutions opens up promising benefits and opportunities for pharmaceutical protein production.